Method for enhancing water decomposition performance of two-dimensional gallium selenide / zirconium disulfide heterojunction based on atomic adsorption

By constructing a gallium selenide/zirconium disulfide heterojunction and adsorbing Se and Zn atoms on its surface, the problem of low photocatalytic efficiency of single-layer materials is solved, and the efficiency of photocatalytic water decomposition and light capture ability are significantly improved.

CN119324015APending Publication Date: 2025-01-17YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310873292.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The monolayer zirconium disulfide and monolayer gallium selenide have low efficiency in photocatalytic water decomposition and cannot effectively utilize sunlight.

Method used

By constructing a gallium selenide/zirconium disulfide heterojunction and adsorbing Se atoms and Zn atoms on the surface of the gallium selenide layer of the heterojunction, the energy band structure is optimized and the photocatalytic performance is improved.

Benefits of technology

Effectively separate electron holes, improve photocatalytic efficiency, enhance light capture ability, and significantly improve water decomposition performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324015A_ABST
    Figure CN119324015A_ABST
Patent Text Reader

Abstract

The invention discloses a method for enhancing the water decomposition performance of a two-dimensional gallium selenide / zirconium disulfide heterojunction based on atomic adsorption, and efficient photocatalytic water decomposition can be realized by constructing a unique atomic adsorption gallium selenide / zirconium disulfide heterojunction structure. According to the provided adsorption enhancement structure, the electronic structure and the energy gap size of the gallium selenide / zirconium disulfide heterojunction can be effectively regulated and controlled by adjusting the number of adsorbed Se atoms and Zn atoms, meanwhile, a Z-type structure is kept, and the oxidation reduction capacity of an electron hole is improved; according to the atomic adsorption enhanced gallium selenide / zirconium disulfide heterojunction, the light capturing capacity is greatly improved, the maximum light absorption coefficient in the visible light range exceeds 1 * 10 < 5 > cm <-1 >, the maximum absorption coefficient in the ultraviolet light range can reach 8 * 10 < 5 > cm <-1 >, and the maximum STH efficiency reaches 51%; se atoms and Zn atoms are adsorbed on the surface of the gallium selenide layer, so that the complete water decomposition capability of the gallium selenide / zirconium disulfide heterojunction can be improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photocatalytic water decomposition, and in particular to a method for enhancing the water decomposition performance of a two-dimensional gallium selenide / zirconium disulfide heterojunction based on atomic adsorption. Background Art

[0002] Since the successful preparation of single-layer graphene, a wave of research on two-dimensional materials has been set off in various fields. Compared with bulk materials, two-dimensional materials have many novel properties in mechanics, electricity, optics and magnetism. Two-dimensional materials also perform well in photocatalytic water decomposition. Two-dimensional materials have a large specific surface area, so there are sufficient active sites distributed on their surface. Not only that, the thickness of two-dimensional materials is only at the nanometer level, so the photogenerated electron holes can migrate to the surface of the two-dimensional material in a short time to undergo redox reactions. In addition, two-dimensional materials have strong light absorption capabilities and can make full use of solar energy to improve the efficiency of water decomposition. The properties of two-dimensional materials are easier to control through strain, electric field, doping and defects.

[0003] Gallium selenide is a typical layered structure. Single-layer gallium selenide has a good on-off current ratio. Its excellent performance has attracted widespread attention in the field of nonlinear optics and optoelectronics. Therefore, the preparation method of single-layer gallium selenide has been quite perfect. Single-layer gallium selenide has a large band gap, and its band edge potential can easily cross the redox potential of water decomposition to achieve water decomposition. However, the large band gap also leads to the inability of single-layer gallium selenide to effectively utilize sunlight, so it cannot be used as an efficient photocatalyst. Single-layer zirconium disulfide has good carrier mobility and thermodynamic stability, and its application in the field of solar cells has been widely studied. Low-pressure chemical vapor deposition and traditional stripping methods can easily prepare single-layer zirconium disulfide. Single-layer zirconium disulfide has a good visible light response, but its band edge position is not suitable for photocatalytic water decomposition. In the present invention, single-layer gallium selenide and zirconium disulfide are stacked to form a Z-type heterojunction, and the light absorption and the redox ability of electrons and holes are enhanced by adsorbing Se atoms and Zn atoms on the surface of the gallium selenide layer of the heterojunction, and its hydrolysis ability is simulated and analyzed by the first-principles calculation method. Summary of the invention

[0004] The present invention provides a method for enhancing the water decomposition performance of a two-dimensional gallium selenide / zirconium disulfide heterojunction based on atomic adsorption, which solves the problem of low water decomposition efficiency of single-layer zirconium disulfide and single-layer gallium selenide in the prior art.

[0005] The technical solution of the present invention is as follows: first, the structure of the single-layer material is optimized so that the lattice mismatch of the two single-layer materials can meet the requirements of forming a heterojunction, the optimized single-layer materials are combined, and heterojunctions of different configurations are designed by changing the stacking method. By calculating the binding energy of the heterojunction, the thermodynamic stability of the heterojunction is determined, and the heterojunction with the lowest binding energy is selected from different heterojunctions, and the structure of this heterojunction is optimized with higher precision. After determining the crystal structure of the heterojunction, the HSE06 functional is used to calculate the band structure and partial wave state density of the heterojunction to determine the band gap and band arrangement of the heterojunction. The charge transfer and built-in electric field at the heterojunction interface are studied and analyzed using the differential charge density method and electrostatic potential energy; the photocatalytic mechanism of the heterojunction is determined by calculating the energy band, built-in electric field, carrier mobility and light absorption of the gallium selenide / zirconium disulfide heterojunction. Se atoms and Zn atoms are adsorbed on the surface of the gallium selenide layer of the heterojunction, and their band structure and band edge position are calculated. The hydrolysis ability of the heterojunction under atomic adsorption is studied. Atomic adsorption can effectively optimize the band structure of the heterojunction and improve the photocatalytic performance.

[0006] The beneficial effects of the present invention are: by constructing a gallium selenide / zirconium disulfide heterojunction, electron holes are effectively separated, thereby improving the efficiency of photocatalysis; The Z-type hydrolysis mechanism of the GaSe / ZrS2 heterojunction improves the redox ability of electron holes; By constructing a GaSe / ZrS2 heterojunction, the light capture capability is greatly improved, thereby increasing the efficiency of photocatalysis. The water splitting ability of the GaSe / ZrS2 heterojunction can be improved by adsorbing Se atoms and Zn atoms on the surface of the GaSe layer. Description of the drawings:

[0008] Figure 1 The side view and top view of different gallium selenide / zirconium disulfide heterogeneous crystal structures in the present invention. (a) GZ-1; (b) GZ-2; (c) GZ-3;

[0009] Figure 2 The projected energy band and partial wave state density of the GaSe / ZrS2 heterojunction in the present invention. (a) Projected energy band; (b) Partial wave state density;

[0010] Figure 3 is a CDD diagram of the gallium selenide / zirconium disulfide heterojunction in the present invention;

[0011] Figure 4 is an electrostatic potential energy diagram of the gallium selenide / zirconium disulfide heterojunction in the present invention;

[0012] Figure 5is the light absorption coefficient of the single-layer gallium selenide, the single-layer zirconium disulfide and the gallium selenide / zirconium disulfide heterojunction in the present invention;

[0013] Figure 6 The crystal structure of the GaSe / ZrS2 heterojunction after adsorption of different atoms in the present invention. (a) Se atom adsorption; (b) Zn atom adsorption;

[0014] Figure 7 The light absorption coefficient diagram of the monolayer hafnium disulfide, monolayer indium selenide and indium selenide / hafnium disulfide heterojunction in the present invention is the projected energy band of the gallium selenide / zirconium disulfide heterojunction after adsorption of different atoms. (a) Se atom adsorption; (b) Zn atom adsorption;

[0015] Figure 8 It is the band edge position of the gallium selenide / zirconium disulfide heterojunction in the present invention after adsorbing different atoms. Specific implementation method:

[0017] Combined with Figure 1-8 The present invention further describes a method for enhancing the water decomposition performance of a two-dimensional gallium selenide / zirconium disulfide heterojunction based on atomic adsorption.

[0018] First, the structure of single-layer gallium selenide and zirconium disulfide was optimized. The lattice constants of the optimized single-layer gallium selenide and zirconium disulfide were 3.82Å and 3.68Å respectively. At this time, the lattice mismatch between the single-layer gallium selenide and zirconium disulfide was calculated to be 3.66%, which meets the requirements for building a heterojunction. The single-layer gallium selenide was placed at the bottom and the single-layer zirconium disulfide was placed at the top. In order to obtain the most stable gallium selenide / zirconium disulfide heterojunction configuration, the gallium selenide layer was fixed and the zirconium disulfide layer was moved. Three gallium selenide / zirconium disulfide heterojunctions with different stacking methods were designed and named GZ-1, GZ-2 and GZ-3. The specific structure is as follows Figure 1 As shown. By calculating the binding energy of the third party, it can be found that GZ-1 has the lowest binding energy, so GZ-1 is the most stable of the three structures, and subsequent research will also focus on GZ-1.

[0019] The projected energy bands of GaSe / ZrS2 heterojunctions calculated using HSE06 hybrid functional are shown in Figure 2. Figure 2 As shown, from Figure 2 It can be seen that GaSe / ZrS2 is an indirect bandgap semiconductor with a bandgap of 1.26 eV. And its band arrangement is type II band arrangement, in which VBM is provided by the GaSe layer and CBM comes from the ZrS2 layer. The bandgap and band arrangement can preliminarily prove that GaSe / ZrS2 can be used for photocatalytic water splitting, because its bandgap and band arrangement type meet the requirements of photocatalytic water splitting.

[0020] When a single layer of material forms vdWH, charge transfer occurs at the interface, and the charge transfer can be clearly described by charge density difference (CDD). The calculation results are as follows: Figure 3 As shown. Figure 3 In the figure, red and green represent charge accumulation and loss, respectively. The CDD of the GaSe layer near the interface is green, indicating charge loss. The CDD near the ZrS2 layer is red, indicating charge accumulation. This means that when the GaSe / ZrS2 heterojunction is formed, charges move from the GaSe layer to the ZrS2 layer. A built-in electric field is formed at the GaSe / ZrS2 interface, pointing from the GaSe layer to the ZrS2 layer. The built-in electric field promotes the movement of carriers and has a significant effect on the photocatalytic performance.

[0021] Figure 4 It is the electrostatic potential energy diagram of the GaSe / ZrS2 heterojunction along the z-axis direction. The electrostatic potential energy diagram can also be used to analyze the electric field at the interface, and the vacuum energy level of the material can also be obtained. As shown in Figure 4, the potential of the GaSe layer at the interface is higher than that of the ZrS2 layer, and the potential difference is 1.36 eV. This potential difference can also prove that there is a built-in electric field from the GaSe layer to the ZrS2 layer at the interface of the GaSe / ZrS2 heterojunction. In addition, after the heterojunction is formed, the vacuum energy level on the GaSe side is the same as the vacuum energy level on the ZrS2 side, so there is no surface potential difference. The work function of the material can be obtained using the vacuum energy level, and the charge transfer at the interface can also be analyzed using the work function. The calculated work functions of the monolayer GaSe and the monolayer ZrS2 are 6.1 eV and 7.4 eV, respectively. The work function of ZrS2 is greater than that of GaSe. Electrons tend to move to a layer with a larger work function, namely the zirconium disulfide layer. The work function also proves that there is a built-in electric field in the GaSe / ZrS2 heterojunction pointing from the GaSe layer to the ZrS2 layer.

[0022] Catalysts are not only affected by energy bands and built-in electric fields, but also by carrier mobility. The DPA method was used to calculate the carrier mobility of monolayer GaSe, monolayer ZrS and GaSe / ZrS heterojunction along the zigzag and armchair directions. The zigzag and armchair directions correspond to the Γ-X and Γ-Y directions in the Brillouin zone, respectively. The electron mobility along the armchair direction in the GaSe / ZrS heterojunction is 360.62 cm 2 V -1 s -1 , the hole mobility is 71.41 cm 2 V -1 s -1 The electron mobility along the zigzag direction is 1450.38 cm2 V -1 s -1 , the hole mobility is 90.40 cm 2 V -1 s -1 . From the above results, it can be seen that the mobility of electrons along the zigzag direction is greatly improved after the heterojunction is formed. In addition, the E1 of the GaSe / ZrS2 heterojunction is also reduced, which is beneficial to improving the carrier mobility. Not only that, in the GaSe / ZrS2 heterojunction, there is a big difference in the mobility of electrons and holes in the same direction, especially along the zigzag direction. This difference in mobility can effectively prevent the recombination of photogenerated carriers and improve the performance of photocatalysis.

[0023] The catalytic performance of photocatalysts depends largely on their light absorption capacity. This means that efficient photocatalysts should have strong light collection capabilities, especially visible light. Because the energy of sunlight is concentrated in visible light, only excellent light absorption in the visible light range can fully utilize solar energy. Figure 5 The light absorption coefficients of single-layer GaSe, single-layer ZrS2, and GaSe / ZrS2 heterojunction are depicted. The blue line is the boundary between the visible light region and the ultraviolet light region, and the red line is the boundary between the visible light region and the infrared light region. In addition, the gray line in the figure represents the solar flux. Figure 5 It can be seen that the light absorption coefficient of single-layer GaSe is relatively high in the ultraviolet range, and the light absorption coefficient at 250 nm reaches 6×10 5 cm -1 However, the light absorption coefficient of a single-layer GaSe is relatively low in the visible light range and infrared light range, especially in the range of 700 nm to 1000 nm. Unlike a single-layer GaSe, a single-layer ZrS2 has a relatively high light absorption coefficient in the visible light range, and has an absorption peak at 500 nm. The coefficient here exceeds 2×10 5 cm -1 However, the light absorption coefficient of a single layer of zirconium disulfide is relatively low in the ultraviolet range. It is worth noting that compared with single layer materials, the GaSe / ZrS2 heterojunction has a higher light absorption coefficient in the entire spectral range. More importantly, the GaSe / ZrS2 heterojunction has a maximum light absorption coefficient of more than 1×10 5 cm -1 , even in the infrared range, it has good light absorption. In the ultraviolet range, the light absorption coefficient can reach up to 8×10 5 cm -1. The GaSe / ZrS2 heterojunction inherits the advantages of single-layer GaSe and single-layer ZrS2 in light absorption, so the GaSe / ZrS2 heterojunction has a strong light capture ability. In addition, the STH efficiency of the GaSe / ZrS2 heterojunction can be calculated to be 51% using the formula, which shows that the GaSe / ZrS2 heterojunction can make full use of sunlight. This also further proves that GaSe / ZrS2 can be used as an efficient photocatalytic heterojunction.

[0024] Atomic adsorption is a method to regulate the electronic structure and photocatalytic performance of 2D materials. Because the adsorption concentration cannot be too high, the heterojunction is first expanded into a 4×4×1 supercell. Then single-atom adsorption is performed on the GaSe layer of the heterojunction. In order to obtain the most stable adsorption position, three sites are selected on the surface of the GaSe layer to adsorb Se atoms and Zn atoms. The three sites are directly below the Ga atom, directly below the Se atom, and directly below the hexagonal center. The binding energy of the three is calculated, and the most stable adsorption model among the three is selected using the binding energy. Figure 6 This is a side view of the crystal structure after the adsorption of Se and Zn atoms. The Se atom is adsorbed directly below the Se atom, and the Se-Se bond length is 2.29 Å. The adsorption of the Se atom affects the Se and Ga atoms around it and changes their positions. The Zn atom is adsorbed directly below the Ga atom, and the Zn-Se bond length is 3.58 Å. The adsorption of the Zn atom does not significantly change the positions of other atoms.

[0025] Figure 7 The projected energy band of the GaSe / ZrS2 heterojunction after the adsorption of Se and Zn atoms. The band gaps of the GaSe / ZrS2 heterojunction after the adsorption of Se and Zn atoms are 0.487 eV and 0.725 eV, respectively. The band gap of the GaSe / ZrS2 heterojunction is significantly reduced after atomic adsorption, which is beneficial to electronic transitions and improves photocatalytic performance. After the adsorption of Se and Zn atoms, an energy band completely occupied by adsorbed atoms appears between the VBM and Fermi level of the heterojunction. The appearance of these impurity states leads to a reduction in the band gap of the heterojunction.

[0026] Figure 8The band edge position of the GaSe / ZrS2 heterojunction after atomic adsorption is plotted. Because the adsorbed atoms are in the GaSe layer, the effect of the adsorbed atoms is counted in the GaSe layer. After the adsorption of Se atoms, the band edge potential of the GaSe / ZrS2 heterojunction still meets the requirements for water decomposition. At this time, the band gap of the GaSe layer is 2.02 eV, which is 1 eV less than when no adsorption is performed. After the adsorption of Zn atoms, the band edge position still meets the requirements for water decomposition. At this time, the band gap of the GaSe layer is 2.47 eV, and the CBM of the GaSe layer still maintains a high potential. After the adsorption of Se and Zn atoms, the band gap of the GaSe / ZrS2 heterojunction is significantly reduced, but the band edge potential is still high. Therefore, the water decomposition ability of the GaSe / ZrS2 heterojunction can be improved by atomic adsorption.

[0027] The above descriptions are only preferred embodiments of the present invention, and all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A method for enhancing the water decomposition performance of a two-dimensional gallium selenide / zirconium disulfide heterojunction based on atomic adsorption, characterized in that: The following steps are included: S1. Optimizing the structure of the single-layer gallium selenide and zirconium disulfide materials so that the lattice mismatch of the two single-layer materials meets the requirements for forming a heterojunction; S2. Combine the optimized single-layer materials and design heterojunctions of different configurations by changing the stacking method; S3. Determine the thermodynamic stability of heterojunctions by calculating the binding energy of heterojunctions of different configurations, select the heterojunction with the lowest binding energy, and perform structural optimization of this heterojunction with higher precision; S4. Use HSE06 functional to calculate the band structure and partial wave state density of the heterojunction with the lowest binding energy, and determine the band gap and band arrangement of the heterojunction; S5. Use the differential charge density method and electrostatic potential energy to study and analyze the charge transfer and built-in electric field at the heterojunction interface; S6. Determine the photocatalytic mechanism of the GaSe / ZrS2 heterojunction by calculating the energy band, built-in electric field, carrier mobility and light absorption of the heterojunction; S7. Se atoms and Zn atoms are adsorbed on the surface of the GaSe layer of the heterojunction, and its band structure and band edge position are calculated to study the hydrolysis ability of the heterojunction under atomic adsorption; S8. It is concluded that atomic adsorption can effectively optimize the band structure of the heterojunction and improve the photocatalytic performance.

2. The method for enhancing the water decomposition performance of a two-dimensional gallium selenide / zirconium disulfide heterojunction based on atomic adsorption according to claim 1, characterized in that: In step S1, the lattice constants of the single-layer gallium selenide and zirconium disulfide materials after material structure optimization are 3.82Å and 3.68Å, respectively, and the lattice mismatch rate of the single-layer gallium selenide and zirconium disulfide materials is 3.66%, which meets the requirements for constructing a heterojunction.

3. The method for enhancing the water decomposition performance of a two-dimensional gallium selenide / zirconium disulfide heterojunction based on atomic adsorption according to claim 1, characterized in that: The binding energy of the GaSe / ZrS2 heterojunction is negative, and the lattice constant is 3.735 Å. The lattice constant of the GaSe / ZrS2 heterojunction is greater than that of a monolayer ZrS2 and smaller than that of a monolayer GaSe. Binding energy calculation method: total energy of heterojunction - total energy of indium selenide - total energy of hafnium disulfide Structural optimization method: first use the conjugate gradient algorithm to perform low-precision atomic position optimization, and then use the quasi-Newton algorithm to perform high-precision atomic position optimization.

4. The method for enhancing the water decomposition performance of a two-dimensional gallium selenide / zirconium disulfide heterojunction based on atomic adsorption according to claim 1, characterized in that: Calculating the band edge position using the work function Work function = vacuum level - Fermi level Light absorption calculation method: